Answers

2014-04-10T17:55:04+05:30
Let the age of son = x years (Today)
So, the age of father = 6x years (Today)
After 20 years, the age of son will be = (x+20) years
After 20 years, the age of father will be (6x+20) years
By the condition,
(6x+20) = 2 (x+20)
or, 6x +20 = 2x + 40
or, 6x-2x = 40-20
0r, 4x = 20
or, x = 20/4 = 5 years
So, today the age of son = 5 years
Toady, the age of father = 5x6 = 30 years
So, when the son was born, the age of father was = (30-5) = 25 years
0
2014-04-10T18:56:31+05:30
Let son age be x years father age will be 6x years after 20 years father age will be 6x + 20 son age will be x + 20 equation formed (6x+20) = 2(x+20) 6x-2x = 40-20 4x= 20 x = 20/4 x = 5 age of son today = 5 years age of father today = 5*6= 30 years age of father when son born 30-5 = 25 years
0